Interstitial and Granulomatous Lung Disease in Inflammatory Bowel Disease Patients. (11th October 2019) - Eliadou, Elena; Moleiro, Joana; Ribaldone, Davide Giuseppe; Astegiano, Marco; Rothfuss, Katja; Taxonera, Carlos; Ghalim, Fahd; Carbonnel, Franck; Verstockt, Bram; Festa, Stefano; Maia, Luís; Berrozpe, Ana; et al.
Abstract: Background: Interstitial lung [ILD] disease and granulomatous lung disease [GLD] are rare respiratory disorders that have been associated with inflammatory bowel disease [IBD]. Clinical presentation is polymorphic and aetiology is unclear. Methods: This was an ECCO-CONFER project. Cases of concomitant ILD or GLD and IBD, or drug-induced ILD/GLD, were collected. The criteria for diagnosing ILD and GLD were based on definitions from the American Thoracic Society and the European Respiratory Society and on the discretion of reporting clinician. Results: We identified 31 patients with ILD. The majority had ulcerative colitis [UC] [ n = 22]. Drug-related ILD was found in 64% of these patients, 25 patients [80.6%] required hospitalisation, and one required non-invasive ventilation. The causative drug was stopped in all drug-related ILD, and 87% of patients received systemic steroids. At follow-up, 16% of patients had no respiratory symptoms, 16% had partial improvement, 55% had ongoing symptoms, and there were no data in 13%. One patient was referred for lung transplantation, and one death from lung fibrosis was reported. We also identified 22 GLD patients: most had Crohn's disease [CD] [ n = 17]. Drug-related GLD was found in 36% of patients and 10 patients [45.4%] required hospitalisation. The causative drug was stopped in all drug-related GLD, and 81% of patients received systemic steroids. Remission of both conditions was achieved in almost all patients. Conclusions: ILD and GLD, although rare, can cause significant morbidity. In our series, over half of cases were drug-related and therefore focused pharmacovigilance is needed to identify and manage these cases.